1997
DOI: 10.1289/ehp.97105s51143
|View full text |Cite
|
Sign up to set email alerts
|

p53, Cip1, and Gadd153 expression following treatment of A549 cells with natural and man-made vitreous fibers.

Abstract: DNA damage induced by chemicals and ionizing radiation is associated with the expression of negative regulators of the cell cycle. The arrest of cells in Gl and G2 phases of the cell cycle provides time for DNA repair. Asbestos fibers are carcinogenic when inhaled by both humans and animals; however, the mechanism by which the fibers exert their effect is unknown. This work was undertaken to determine whether the expression of DNA damage-inducible genes differs between crocidolite, a fiber positive for lung tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Asbestos-induced p53 protein expression was first evident at 4 h and remained elevated at 24 h (Figure 4). These findings are consistent with the work of others showing that asbestos induces A549 and mesothelial cell p53 expression, upregulates p21 (a downstream gene activated by p53), inhibits cellular proliferation, and promotes apoptosis (17)(18)(19). Similar to these studies, we have observed that amosite asbestos causes dose-dependent inhibition of A549 cell proliferation as assessed by a colony forming unit assay (unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Asbestos-induced p53 protein expression was first evident at 4 h and remained elevated at 24 h (Figure 4). These findings are consistent with the work of others showing that asbestos induces A549 and mesothelial cell p53 expression, upregulates p21 (a downstream gene activated by p53), inhibits cellular proliferation, and promotes apoptosis (17)(18)(19). Similar to these studies, we have observed that amosite asbestos causes dose-dependent inhibition of A549 cell proliferation as assessed by a colony forming unit assay (unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
“…Increased p53 protein expression occurs in the bronchiolar and alveolar epithelium of humans with idiopathic pulmonary fibrosis and in rodents exposed to asbestos (14)(15)(16). It is established that asbestos induces p53 and p21 expression in lung epithelial and mesothelial cells and that this results in cell cycle arrest (17)(18)(19). Crocidolite asbestos induces p53 gene mutations predominantly in exons 9 through 11 in BALB/c-3T3 cells (20).…”
mentioning
confidence: 99%
“…Asbestos activates p53 and p21 expression in lung epithelial and mesothelial cells that result in cell-cycle arrest (104108). Furthermore, increased p53 levels are detected in lung cancers of patients with asbestosis (109), and p53 point mutations are present in the lung epithelium of smokers and asbestos-exposed individuals (110).…”
Section: Role Of P53 In Asbestos Pulmonary Toxicitymentioning
confidence: 99%
“…JOHNSON et al [44] demonstrated that exposure of A549 cells to asbestos fibres induced a dosedependent increase in the G2 phase cell numbers. Aneuploidy was associated with an increase in the protein levels of genes such as p53, Cip1 and Gadd45, which are induced by DNA damage.…”
Section: Nanoparticle-driven Carcinogenesis Pathways Rm Mroz Et Almentioning
confidence: 99%